2018
DOI: 10.7554/elife.36144
|View full text |Cite
|
Sign up to set email alerts
|

TALE factors use two distinct functional modes to control an essential zebrafish gene expression program

Abstract: TALE factors are broadly expressed embryonically and known to function in complexes with transcription factors (TFs) like Hox proteins at gastrula/segmentation stages, but it is unclear if such generally expressed factors act by the same mechanism throughout embryogenesis. We identify a TALE-dependent gene regulatory network (GRN) required for anterior development and detect TALE occupancy associated with this GRN throughout embryogenesis. At blastula stages, we uncover a novel functional mode for TALE factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 91 publications
(165 reference statements)
6
31
0
Order By: Relevance
“…Many of these sites are also occupied by nucleosomes, consistent with previous reports that Pbx TFs possess pioneer activity (Magnani et al, 2011). While we find maternally deposited TALE TFs bound at genomic elements near genes activated at ZGA, they are also bound near genes active later in development (Ladam et al, 2018), suggesting that TALE TFs may have a dual role. Notably, we further demonstrated that a subset of TALE-occupied sites is associated with nearby binding motifs for the NF-Y TF.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Many of these sites are also occupied by nucleosomes, consistent with previous reports that Pbx TFs possess pioneer activity (Magnani et al, 2011). While we find maternally deposited TALE TFs bound at genomic elements near genes activated at ZGA, they are also bound near genes active later in development (Ladam et al, 2018), suggesting that TALE TFs may have a dual role. Notably, we further demonstrated that a subset of TALE-occupied sites is associated with nearby binding motifs for the NF-Y TF.…”
Section: Introductionsupporting
confidence: 90%
“…in gastrulation or organogenesis) also act at the ZGA. Accordingly, we recently reported that two TFs of the TALE family (Prep1 and Pbx4) -that were originally defined as cooperating with Hox proteins in the activation of tissue-specific gene expression during organogenesis -actually occupy their genomic binding sites already during maternal stages of zebrafish embryogenesis (Ladam et al, 2018). Many of these sites are also occupied by nucleosomes, consistent with previous reports that Pbx TFs possess pioneer activity (Magnani et al, 2011).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…One such candidate factor is NFYA. It has previously been shown that NFYA binds to DNA in combination with TALE factors during zebrafish blastula stages [68], promotes chromatin accessibility and enhances the binding of Oct4, Sox2 and Nanog in embryonic stem cells [69], and establishes open chromatin during mouse ZGA [11]. Future studies will reveal whether NFYA cooperates with Pou5f3, Sox19b and Nanog in transcriptional priming during zebrafish ZGA.…”
Section: Pou5f3 Sox19b and Nanog Establish Chromatin Accessibilitymentioning
confidence: 87%